An Analysis of Idiomatic Expressions Found in “A Real Pain” Movie: Penelitian - Winda Ayu Saraszeta; AB. Prabowo K.A.; Sukma Nur Ardini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research analysis idiomatic expressions found in the Movie “A Real Pain” (2024) directed by Jesse Eisenberg. The study aims to identify, classify, and describe the dominant types of idiomatic expressions used in the Movie. A qualitative descriptive method was employed, focusing on the transcription of dialogues as the main data source. The analysis applied McCarthy and O’Dell’s (2002) framework, which categorizes idioms into eight types: phrasal verb idioms, proverbs or fixed statements, binomial expressions, similes, euphemisms, trinomial expressions, clichés, and other language idioms. The findings reveal a total of 45 idiomatic expressions distributed across these categories. Among them, phrasal verb idioms are the most frequently used, representing 35.6% of the total data. These idioms often function to convey emotions, emphasize character traits, and enhance the natural flow of conversation. The study also found that idiomatic expressions in “A Real Pain” serve not only as linguistic embellishments but also as pragmatic tools for expressing cultural identity, emotional nuance, and interpersonal relationships within the narrative. In conclusion, idiomatic expressions play a vital role in enriching the Movie’s dialogue and demonstrating authentic use of contemporary American English.